2021
DOI: 10.3171/2020.1.jns192787
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postoperative measurement of thyroid-stimulating hormone as an early predictor of remission in thyroid-stimulating hormone–secreting pituitary adenomas

Abstract: OBJECTIVEThyroid-stimulating hormone (TSH)–secreting pituitary adenoma (TSHoma) is a rare type of pituitary adenoma; thus, little is known about TSHomas. The purpose of this study was to analyze clinical characteristics and therapeutic outcomes of TSHomas based on a single-center experience. The authors also searched for reliable preoperative and early postoperative factors that could predict long-term endocrinological remission. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
13
1
3
Order By: Relevance
“…1 , the PubMed/Medline search provided 3238 articles to which none were added through other sources. After duplicate removal ( n = 35), 3203 records were screened and 294 were assessed for eligibility through full-text screening, concluding 40 studies included in qualitative synthesis, all of which were also eligible for quantitative meta-analysis [ 2 , 6 10 , 12 , 14 , 17 , 21 , 27 , 29 , 31 , 34 , 40 , 42 , 47 , 48 , 51 53 , 55 , 57 59 , 67 , 68 , 75 , 78 , 79 , 81 , 83 , 86 , 89 , 91 – 96 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , the PubMed/Medline search provided 3238 articles to which none were added through other sources. After duplicate removal ( n = 35), 3203 records were screened and 294 were assessed for eligibility through full-text screening, concluding 40 studies included in qualitative synthesis, all of which were also eligible for quantitative meta-analysis [ 2 , 6 10 , 12 , 14 , 17 , 21 , 27 , 29 , 31 , 34 , 40 , 42 , 47 , 48 , 51 53 , 55 , 57 59 , 67 , 68 , 75 , 78 , 79 , 81 , 83 , 86 , 89 , 91 – 96 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The details of the 40 included studies are summarized in Table 1 . We identified 31 studies reporting postoperative biochemical remission [ 2 , 6 , 8 , 10 , 12 , 14 , 21 , 29 , 31 , 34 , 40 , 42 , 47 , 48 , 51 53 , 55 , 57 59 , 67 , 68 , 75 , 78 , 79 , 81 , 86 , 89 , 92 , 94 ], eight reporting rate of GTR [ 7 , 17 , 27 , 68 , 75 , 91 , 94 , 95 ], five reporting incidence of postoperative diabetes insipidus (DI) [ 7 , 21 , 58 , 83 , 93 ], four reporting preoperative levels of prolactin [ 21 , 67 , 94 , 96 ], one study reporting rate of postoperative hyperprolactinemia [ 94 ], one study reporting both postoperative adrenocorticotropic hormone (ACTH) and thyroid-stimulating hormone (TSH) deficiency [ 9 ], one study reporting postoperative panhypopituitarism [ 83 ], and one study reporting any endocrinological deficit [ 55 ], while each of those endpoints was stratified by gender. No studies were found that reported preoperative levels of testosterone or estrogen, postoperative follicle-stimulating hormone (FSH), luteinizing hormone (LH) deficiency, growth hormone (GH) deficiency, or postoperative rate of syndrome of inappropriate antidiuretic hormone secretion (SIADH) by gender.…”
Section: Resultsmentioning
confidence: 99%
“…Since normal lactotrophs are suppressed by prolonged negative feedback, prolactin levels should decrease to a subnormal level in cases of radical tumor removal [ 22 ]. We previously demonstrated that immediate postoperative measurement of hypersecreting hormones reliably predicts long-term remission in acromegaly and thyroid-stimulating hormone-secreting pituitary adenoma models [ 23 24 ]. We hypothesized that this predictive modeling system may also be useful for patients with surgically treated prolactinoma.…”
Section: Discussionmentioning
confidence: 99%
“…If only major complications were considered, interventions on brous adenomas seem to have a more signi cant number of complications according to the univariate model (Table 4), despite having passed the learning curve. This may be mainly due to the fact that surgical removal in these tumors is more complex, requiring greater glandular manipulation[6] and, in many cases, an extracapsular dissection [31].…”
Section: Discussionmentioning
confidence: 99%